2020
DOI: 10.1186/s12882-020-01755-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and epidemiology of acute kidney injury in a pediatric Malawian trauma cohort: a prospective observational study

Abstract: Background: Acute kidney injury (AKI) is highly associated with mortality risk in children worldwide. Trauma can lead to AKI and is a leading cause of pediatric death in Africa. However, there is no information regarding the epidemiology of pediatric, trauma-associated AKI in Africa.Methods: Prospective cohort study of pediatric trauma patients admitted to a tertiary referral hospital in Malawi. Participants enrolled at admission were followed prospectively throughout their hospitalization. AKI was defined by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
(50 reference statements)
3
11
0
Order By: Relevance
“…Respiratory, circulatory, hematologic, or oncologic status and infection are common causes for critical diseases ( 13 ) and CPA ( 1 , 3 , 11 ) in PICU, because they could induce severe hypoxemia, hypovolemia, acid-base disturbance, and multiple organ disease syndrome. Similar to previous studies ( 1 , 3 , 9 , 14 ), our results showed that respiratory and circulatory diseases were the major contributors to CPA. Trauma was rarely mentioned in previous reports on the characteristics of CPA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Respiratory, circulatory, hematologic, or oncologic status and infection are common causes for critical diseases ( 13 ) and CPA ( 1 , 3 , 11 ) in PICU, because they could induce severe hypoxemia, hypovolemia, acid-base disturbance, and multiple organ disease syndrome. Similar to previous studies ( 1 , 3 , 9 , 14 ), our results showed that respiratory and circulatory diseases were the major contributors to CPA. Trauma was rarely mentioned in previous reports on the characteristics of CPA.…”
Section: Discussionsupporting
confidence: 91%
“…Our results showed that the ROSC of trauma was 50%, but only 16.7% had survived to discharge. We made no further analysis about the exact cause of death in trauma, but trauma-associated respiratory ( 16 ) and renal injury ( 14 ) were attributed to increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to other studies in South Africa and high-income settings [8,[31][32][33]. This increased risk of mortality was also seen in our previous analysis of pediatric trauma patients [15]. As Malawi has one of the highest rates of road traffic injuries in the world [34,35], confirming that trauma leads to high AKI rates in lowincome settings is important as this may be an intervenable target to improve trauma-related mortality.…”
Section: Table 2 Socioeconomic Status Variables Among Adult Trauma Patients By Development Of Aki In Malawisupporting
confidence: 90%
“…For our prospective study, we included all admitted patients with an expected admission > 24 h, and this analysis focuses on the adult patients (> 18 years of age). The pediatric analysis has already been published [15]. Informed consent was obtained from all patients, or if they had altered mental status, a guardian needed to be present and informed consent obtained within 18 h of patient arrival.…”
Section: Patientsmentioning
confidence: 99%
“…The global prevalence of chronic kidney disease (CKD) is estimated at approximately 13.4%, while estimates suggest that acute kidney injury (AKI) affects approximately 13.3 million people globally every year [ 1 , 2 ]. According to the Global Burden of Disease study in 2017, 1.2 million deaths were attributed to CKD, and it was the 12th leading cause of death worldwide [ 3 ].…”
Section: Introductionmentioning
confidence: 99%